Seeking For The True Love In Mike Newell's Love In TheTime Of Cholera (2007): An Individual Psychological Approach - Istiqomah, Rutha Tyana, Drs. M. Thoyibi, M.S, TitisSetyabudi S.S., M.Hum (2013)
The major problem of this study is how seeking for the true love is reflected in Love in the Time of Choleramovie based on individual psychological approach. This study analyze the structural elements in Love in the Time of Cholera movie and Florentino Ariza's seeking for the true love based on individual psychological point of view. In analyzing the movie, the researcher uses qualitative study. The object of the study is Florentino Ariza. The primary data is Love in the Time of Choleramovie itself. The secondary data are script of the movie and internet websites related to the study. The method of collecting data is purpose sampling by watching carefully the movie and then the researcher took of sample dialogue and picture of the movie then used it as a starting point to analyze the issue. The technique of data analysis is descriptive technique. A result of the analysis shows the following conclusion: first, based on the structural analysis it can be concluded that in Love in the Time of Cholera movie Mike Newell conveys analysis that love is blind. Second, based on the psychological analysis. It is evident that in this movie Mike Newell illustrates the close relationship between literature and psychology by presenting that the individual is obsessed with love